KERJA SAMA TIONGKOK DAN INDONESIA DALAM PENGEMBANGAN MOBIL LISTRIK - Emmanuela Angely Pardede; Hasna Wijayati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study analyzes bilateral cooperation between China and Indonesia in the development of electric cars from 2023 to 2024. Inspired by the global transition to electric vehicles and Indonesia's commitment to reducing greenhouse gas emissions, the study examines how the two countries collaborate to leverage their respective strengths. The descriptive qualitative research method is used through a literature review. The results of the study show that this cooperation is realized in several aspects, namely, investment in nickel resources as a raw material for batteries, strengthening human resources through training and technology transfer programs, and electric car production partnerships with large companies such as BYD, CATL, Geely Auto Group, and Wuling. This collaboration aims not only to accelerate the development of the electric car ecosystem in Indonesia, but also to address local infrastructure and technology challenges, as well as contribute to reducing carbon emissions. The cooperation is also based on the theory of bilateral diplomacy and comparative excellence in international trade, creating mutually beneficial dependency and promoting sustainable economic growth.